VALUE SYSTEM OF CYBER ATHLETES REPRESENTING VARIOUS GAME ARCHETYPES - Kosmina E.A.; Ashkinazi S.M.; Sytnik G.V.; Chernaya A.I. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to determine the value orientations of cyber athletes and identify relationships with the dominant gaming psychotype. Methods and structure of the study. Diagnostics included filling out a portrait questionnaire of the structure of value orientations, a questionnaire of hardiness, a test to identify the dominant player psychotype. The obtained empirical data were subjected to correlation analysis. Results and conclusions. Cyber ​​athletes with the dominant psychotype of "careerist" show an orientation toward external achievements and a low level of involvement in terms of hardiness, "researchers" are focused on the process of cognition, "dominators" prefer to achieve superiority over other players, "socialists" are focused on local interpersonal interactions, with minimal emphasis on positive changes in society.